Fiddler crabs of the world : Ocypodidae : genus Uca - Crane, Jocelyn (Princeton legacy library., 1975)
Jocelyn Crane presents a survey of the members of the genus Uca, with special reference to their morphology, social behavior, and evolution. Her account is firmly based on numerous field studies along the world's warmer shores and on comparative work in laboratories and museums. Originally published in 1975. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting the.